EVALUATION OF GENETIC VARIABILITY OF FRESHWATER PRAWN COLLECTED FROM MAKASSAR-SULAWESI, PANGKALANBUNKALIMANTAN, JAMBI-SUMATRA, SUKABUMI-JAVA, AND GIMacro USING mtDNA CO-I MARKERS - Estu Nugroho; Mulyasari Mulyasari; Anang Hari Kristanto; Fauzan Ali; Gunawan Gunawan (Indonesian Aquaculture Journal, 2008)
The objective of this research is to evaluate the genetic variability of freshwater prawn, Macrobrachium rosenbergii. The genetic variability of freshwater prawn collected from Makassar-Sulawesi, Pangkalanbun-Kalimantan, Jambi-Sumatra, Sukabumi-Java, and GIMacro strain was examined using polymorphism of the mitochondria DNA (mtDNA) markers. Twelve composite haplotypes were detected following digestion of CO1 sequences with four endonucleases: Hae III, Rsa I, Mbo I, and Taq I. The average haplotype diversity was 0.217. Significant genetic difference was observed among freshwater prawn populations, especially among Makassar-Sulawesi population and others. Makassar-Sulawesi strain has future prospect for genetic resources in breeding program.